Work and Welfare as Determinants of Female Poverty and Household Headship - Danziger, Sheldon; Jakubson, George; Schwartz, Saul; Smolensky, Eugene (Quarterly Journal of Economics, 1982)
This paper formulates and estimates a model of the determinants of female household headship. Headship responds to variations in the levels of well-being a woman can expect if she marries or if she heads her own household. We measure the opportunity cost of female headship and the effects of welfare benefits and women's work in the market on female headship and poverty. We find that if welfare benefits were reduced, there would be small reductions in the proportion of women heading households for whites and nonwhites, but a substantial increase in poverty for nonwhites. We also find that wives' work in the market reduces poverty and female headship for nonwhites, and reduces poverty, but increases headship for whites.